Study on the use of Artemia salina as bioindicator in the ecotoxicological evaluation of landfill leachate - Thode Filho, Sérgio; Jorge, Emanuele Nunes de Lima Figueiredo; Oliveira, Aline Santos de; Marques, Monica Regina da Costa; Franco, Heider Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Landfill leachate deserves special attention because it presents itself as a potentially polluting liquid that can attack nearby natural resources if it is not carefully treated and disposed of in a controlled manner, or it may be reused in other activities. The present work had the objective of evaluating the toxicity of untreated landfill leachate on the test organism A. salina. The physical chemical characterization of the landfill leachate for the presence of metals and salts was performed according to the methodology proposed by the American Public Health Association - APHA (2005). After hatching, about 10 nauples of A. salina were transferred to 15 x 150 mm test tubes containing 10 mL (saline water and the landfill leach to be tested). Seven treatments with four replicates were used. The LC5048h of the landfill leachate used in the present study was mathematically obtained in the dose with 28.4% of leachate. The parameters of salinity, ammonia and sulfates are directly related to the value of the LC5048h.